2016
DOI: 10.1021/acs.est.6b03260
|View full text |Cite|
|
Sign up to set email alerts
|

Role of Settling Particles on Mercury Methylation in the Oxic Water Column of Freshwater Systems

Abstract: As the methylation of inorganic mercury to neurotoxic methylmercury has been attributed to the activity of anaerobic bacteria, the formation of methylmercury in the oxic water column of marine ecosystems has puzzled scientists over the past years. Here we show for the first time that methylmercury can be produced in particles sinking through oxygenated water column of lakes. Total mercury and methylmercury concentrations were measured in the settling particles and in surface sediments of the largest freshwater… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

9
56
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 97 publications
(67 citation statements)
references
References 70 publications
(122 reference statements)
9
56
0
Order By: Relevance
“…Furthermore, these authors hypothesize that active water‐column methylation by bacteria is stimulated by redox microniches caused by enhanced degradation of terrestrial DOM. Similar, Gascón Díez et al () emphasize the importance of Hg methylation in suboxic/anerobic microzones in sinking algae derived OM particles in Lake Geneva. However, total Hg in sinking particles in Lake Geneva was not significantly different from that in surface sediments, although MeHg concentrations were 10‐fold higher.…”
Section: Resultsmentioning
confidence: 55%
See 1 more Smart Citation
“…Furthermore, these authors hypothesize that active water‐column methylation by bacteria is stimulated by redox microniches caused by enhanced degradation of terrestrial DOM. Similar, Gascón Díez et al () emphasize the importance of Hg methylation in suboxic/anerobic microzones in sinking algae derived OM particles in Lake Geneva. However, total Hg in sinking particles in Lake Geneva was not significantly different from that in surface sediments, although MeHg concentrations were 10‐fold higher.…”
Section: Resultsmentioning
confidence: 55%
“…However, recent studies have emphasized the importance of DOM‐bound MeHg as well as the quality of DOM (terrestrial vs. marine) for Hg enrichment in plankton (Jonsson et al ; Schartup et al a,b and the literature therein). Oxic water‐column Hg methylation has been found to be a major process increasing MeHg concentrations in settling particles (Balcom et al ; Gascón Díez et al ). Moreover, eutrophication has been shown to increase phytoplankton MeHg concentrations in marine systems and the export of organically bound Hg to the sediment, simultaneously decreasing the water phase Hg reservoir (Soerensen et al ).…”
mentioning
confidence: 99%
“…Nonetheless, several studies revealed that Hg II ‐methylation can occur in oxygen deficient zones of water column (Eckley et al ; Malcolm et al ), sediments (Drott et al ; Hines et al ; Bouchet et al ; Jonsson et al ; Bravo et al ; Liem‐Nguyen et al ) flooded soils, e.g., wetlands (Louis et al ; Tjerngren et al ; Windham‐Myers et al ) and ponds (Lehnherr et al ; MacMillan et al ; Herrero Ortega et al ). In recent years, Hg II ‐methylation processes were in addition observed in microenvironments such as periphyton, growing on macrophytes (Cleckner et al ; Mauro et al ; Guimarães et al ; Achá et al ; Hamelin et al ; Bouchet et al ) and settling particles of oxic water columns, including pelagic ocean waters (Monperrus et al ; Cossa et al ; Sunderland et al ;Lehnherr et al ; Gascón Díez et al ). Initially, MMHg formation in oxic waters was considered negligible due to high redox and low concentrations of bacteria and nutrients, but studies demonstrated that about 20–40% of the MMHg measured below the surface mixed layer originates from the surface and enters deeper ocean waters (Blum et al ).…”
Section: Methylmercury Formation Is Widespread In the Environmentmentioning
confidence: 99%
“…Moreover, a recent study assessing 243 metagenomes from the Tara Oceans expedition reported high abundances of hgcAB genes in 77 samples across all oceans (Villar et al ). The progress in genetics (Gilmour et al ; Parks et al ; Podar et al ; Bravo et al , a ; Liu et al ; Jones et al ) combined with recent advances in the use of stable isotopes to determine Hg II methylation rate constants in sediments (Monperrus et al ; Jonsson et al ; Bravo et al , ), lakes (Eckley and Hintelmann ), water columns and oceans (Munson et al ) as well as in sinking particles of marine and lake waters (Lehnherr et al ; Gascón Díez et al ) have demonstrated that the potential for MMHg formation in the environment is widespread across ecosystems.…”
Section: Methylmercury Formation Is Widespread In the Environmentmentioning
confidence: 99%
“…MeHg is produced in oxygen-limited sediments, soils, and stratified water columns (Pak and Bartha 1998;Eckley and Hintelmann 2006;Gascon Diez et al 2016). The content and composition of NOM and several additional environmental factors such as temperature, redox potential, pH, and sulfur chemistry modulate biological methylation rates of inorganic divalent mercury (Hg(II)) (Ullrich et al 2001;Drott et al 2007).…”
Section: Introductionmentioning
confidence: 99%